Unlocking the Power of Inquiry: A Case Study on Elementary Science Professional Development Program - Ramla Hozefa Poonawala (Research in Social Sciences and Technology- OpenED Network, 2018)
This study examines the awareness of inquiry based teaching amongst elementary science teachers through a workshop intervention, conducted in a private school in Karachi, Pakistan. The case study design deployed, highlighted the learning experiences of 24 participants that took part in the professional development workshop. A qualitative survey was carried before the intervention followed by focus group discussion, document analysis and participant observations during and after the intervention. These methodologies were used to record participants learning experiences and awareness of essential features of inquiry based pedagogy. In addition to this, four primary science teachers were interviewed to examine the adoption of essential features of inquiry in their revised lesson plans. The findings of this study were that before the science training the participants were superficially aware of the fundamentals of inquiry based methods and techniques and knew its importance. However, the in-depth process knowledge and skills/strategies required for an effective inquiry was an identifiable shortcoming. The workshop provided learning opportunities to analyze phenomenon, think scientifically, engage in hands-on science activities. Because of the workshop, the participants demonstrated an improved understanding of what entails an inquiry process and features of scientific inquiry. This research should inspire and inform professional developers about gap in inquiry based science teachings. Furthermore, the study aims to motivate private schools in Pakistan to invest in inquiry based science teaching as a tangible long-term benefit which can translate into better teaching practitioner.